P-ANCA Systemic Vasculitis Induced by Brucellosis in an Elderly Male Patient - Mohammed Cheikh; Abdulrahman Kabli; Esraa Sendi; Hani Almoallim (Case Reports in Rheumatology)
One of the most prevalent causes of vasculitis is bacterial infection. An infection that causes anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is uncommon and not reported frequently. We report a case of a 74-year-old male who presented with fever for ten days and was found to have brucellosis. Then, he was diagnosed with Guillain-Barré syndrome (GBS) and started on immunoglobulin (IVIG) for one week without a response. His fever was still persistent despite appropriate antibiotic therapy. Rheumatology evaluation revealed a history of multiple joint pain and swelling, elevated inflammatory marker, and a high titer of P-ANCA. Steroid therapy was started initially on the background of antibiotics therapy. His fever and other symptoms showed marked improvement after one week. However, P-ANCA titer was still elevated. The decision was made to treat the patient as a case of brucellosis-induced P-ANCA vasculitis. Azathioprine was added, and steroid was maintained for one month and then it was tapered gradually. All symptoms improved from the third month of follow-up except weakness from peripheral neuropathy with normalization of P-ANCA titer. His condition remained stable after six months of follow-up. Clinicians should be aware of the possibility of infection-induced vasculitis, particularly when patients’ symptoms persist despite the appropriate use of antibiotics.